BUSINESS MODEL CANVAS PERUSAHAAN PENGOLAH RUMPUT LAUT - Ammar Fathin Mahdi; Lukman Mohammad Baga (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2018)
Winner Perkasa Indonesia Unggul is a SME that sells product based on seaweed processing. The enterprise is trying to improve their business activity on seaweed processing products. The purposes of this research are to identify the existing business model at the enterprise, to evaluate the model, and to generate a new business model prototype with the Business Model Canvas method analysis. This research is a case study on a company, and conducted in March-May 2016. The data used are primary data in the form of interviews and internal company data, while qualitative analysis used to evaluate the business model, and the SWOT analysis method used to help generating new business model prototype. The results of this research were two alternative of business model prototype for the enterprise’s development in the future. The first alternative is trying to classify new customer segment, and followed by creating the new value proposition. With the additional of new customer segment and the new value proposition, it caused the enterprise to extend the channels by optimalizing technologies, and eventually increase the revenue stream of the enterprise. The second alternative is trying to increase the customer relationship by creating the new value proposition. It will raise the opportunity to make an alliance or partnership for helping the business activity of the enterprise. However, the changes on some parts of the business model will affect the enterprise’s cost structure.